INVESTIGATION OF THE CHARACTERISTICS OF CLOSED-LOOP NON-INVERTING OPERATIONAL AMPLIFIER AT AN EXTENDED FREQUENCY RANGE - Bilienskis, Igoris; Ivach, Vadim (PROFESSIONAL STUDIES: Theory And Practice, 2022)
This article encompasses the description along with the theory of non-inverting operational amplifiers and compares theoretical characteristics with those obtained in the laboratory. The goal is to validate the tendency of the input-output voltage relationship at a fixed 1.25 kHz frequency and the tendency of the gain-frequency relationship based on an officially recognized hypothesis using KL-900A Basic Communication Trainer. The literature on noninverting amplifier characteristics is provided considering the ideal case scenarios which, to some extent, deviate from their practical characteristics. Also, the frequency that could be applied to the non-inverting operational amplifier circuit KL-900A module is limited to 200 kHz. For this reason, the experiment at an extended frequency range varying from 20 Hz to 1.7 MHz was conducted to see either the discrepancy or partial conformity of the operational amplifier characteristics theory and comment on factors that influence the deviation of acquired parameters from ideal parameters and highlight the usefulness of having an extended frequency range for KL-900A Basic Communication Trainer